Modality-Dependent Brain Activation Changes Induced by Acquiring a Second Language Abroad - Sakai, Kuniyoshi L.; Kuwamoto, Tatsuro; Yagi, Satoma; Matsuya, Kyohei (Frontiers in Behavioral Neuroscience, 2021)
The dynamic nature of cortical activation changes during language acquisition, including second-language learning, has not been fully elucidated. In this study, we administered two sets of reading and listening tests (Pre and Post) to participants who had begun to learn Japanese abroad. The two sets were separated by an interval of about two months of Japanese language training. We compared the results of longitudinal functional MRI experiments between the two time points, and obtained the following major findings. First, the left-dominant language areas, as well as bilateral visual and auditory areas, were activated, demonstrating the synergistic effects of multiple modalities. There was also significant activation in the bilateral hippocampi, indicating the expected involvement of memory-related processes. Secondly, in accordance with the behavioral improvements from Pre to Post, the brain activations decreased in the left inferior and middle frontal gyri during the listening tests, as well as in the visual areas (the bilateral inferior and superior parietal lobules, and left inferior and middle occipital gyri) during the reading tests, while activations in the right superior and middle temporal gyri increased during the listening tests. These modality-dependent activation changes could not be explained by domain-general cognitive factors, such as habituation or familiarization, because we used completely different test sets for Pre and Post. Thirdly, the posterior hippocampus showed a main effect of hemisphere, whereas the anterior hippocampus showed a significant main effect of event (i.e., specific to first listening events), reflecting initial encoding of auditory information alone. In summary, activation changes from Pre to Post indicate functional changes in modality-dependent networks over a short period of staying abroad, which would enable effective acquisition in a second language.